RESILIENSI DAN TRANSFORMASI KOMUNIKASI KEPEMIMPINAN PEREMPUAN PESANTREN: DARI TRADISIONAL KE SEKULER DI ERA POSTMODERNISME - Nurul Azizah; Mohammad Armoyu; Joseph Okwesili Nkwede (Maddah : Jurnal Komunikasi dan Konseling Islam, 2024)
The era of globalization and modernism has colored the movement of Islamic boarding school women to appear in the public sector, but at the same time they are required to successfully carry out their duties as housewives. Conventionally, postmodernist feminist construction is in the dual role of Islamic boarding school wo men in the family and public sector, namely women who have a Islamic boarding school background in the field of religion or people who gain legitimacy as teachers or mothers. The Islamic boarding school women's movement is top - down because the production o f religious knowledge and truth is determined by the religious elite so that the public becomes an object that must submit to the elite. The era of new religious movements changed the tendency of Islamic boarding school women's thinking paradigm from the d omestic area to shift to public spaces such as becoming regional heads after the direct regional head election (pilkada) system in Indonesia. This paper aims to analyze the movement of Islamic boarding school women in the postmodern era in managing their d ual roles as housewives and career women in the public domain. From descriptive and content analysis of qualitative research data, it shows that the postmodern Islamic boarding school women's movement is able to shift the religious paradigm from traditiona l conventionalism to modern secularism. The conclusion of this article is about the election of Islamic boarding school women as regional heads, showing the collapse of patriarchal culture in the current postmodern era. This article provides suggestions th at affirmative action is needed for women to improve education, so that they are able to take part in the development of the nation and state